inggris - Kawakibud Durriya; Ruslin Anwar; Eko Andi (Jurnal Penelitian Pendidikan IPA, 2024)
Feasibility studies are essential tools used to assess the viability and potential success of a project or investment. These studies provide critical information that helps stakeholders make informed decisions by analyzing various factors such as costs, benefits, risks, and potential returns. One specific type of project that often undergoes feasibility evaluation is housing development. In many cases, the feasibility assessment of housing projects is typically conducted by estimating the number of units sold without necessarily examining actual sales data. This approach can lead to inaccuracies and misguided conclusions. To address this gap, our research aims to re-evaluate the investment feasibility of ongoing housing projects by incorporating actual sales data and predicting future sales figures. By doing so, we can provide a more accurate and reliable assessment of the project's viability. The findings from this re-evaluation indicate that the investment in housing development remains highly feasible. Key financial metrics support this conclusion: the project has a Payback Period (PP) of just 0.55 years, meaning the initial investment is recovered in a little over half a year. Additionally, the Net Present Value (NPV) stands at Rp 103,917,111,414, reflecting the project's substantial profitability. Furthermore, the Internal Rate of Return (IRR) is an impressive 81.73%, far exceeding typical investment benchmarks. Lastly, the Benefit-Cost Ratio (BCR) of 1.53 demonstrates that the benefits of the project significantly outweigh the costs, confirming its overall financial soundness. These results underscore the importance of using comprehensive data analysis in feasibility studies to ensure accurate and effective investment decisions.